Decentralized control mechanism for body–limb coordination in quadruped running. (June 2020) - Fukuhara, Akira; Koizumi, Yukihiro; Suzuki, Shura; Kano, Takeshi; Ishiguro, Akio
As a mechanism for survival, quadrupeds have obtained skills involving coordination between limbs and the body (i.e. body–limb coordination), providing fast and adaptive locomotion compared with motion using only limbs. Several bio-inspired robotics studies have resulted in the development of legged robots that utilize a flexible spine, similar to cheetahs. However, the control principle of body–limb coordination has not been established to date. From the perspective of a decentralized control scheme, a minimal body–limb coordination mechanism is proposed in this study, in which body parts aid each other via a sensory feedback mechanism. The two-dimensional simulation and hardware experiments reveal that bilateral sensory feedback between limbs and body is essential for the robot to adaptively generate a body–limb coordination pattern and achieve faster locomotion speed than that by only limbs in efficient manner.